Ovicidal and larvicidal effects of extracts from leaves of Andrographis paniculata (Burm. f.) Wall.ex Nees against field isolates of human hookworm (Ancylostoma duodenale). (10th May 2019) - Banerjee, Tuhina; Singh, Aradhana; Kumar, Satyanshu; Dhanani, Tushar; Gajbhiye, N.A.; Koley, Tanmay Kumar; Maurya, Arti; Filgona, Joel
Abstract: Ethnopharmacological relevance: The whole plant of Andrographis paniculata (Burm. f.) Wall.ex Nees is used traditionally in different forms by the local people of Asian countries owing to its myriad medicinal properties. Its use as an anthelmintic has been mentioned in literature but has not been well elucidated. Aim of the study: To determine anthelmintic effects of extracts from leaves of A.paniculata against human hookworm species based on a standard assay system and to establish the effects of major active compounds responsible for the effects. Materials and methods: Ovicidal and larvicidal activities of extracts of leaves of A.paniculata in different solvents ethanol (Et), methanol (Met), ethyl acetate (EA) and petroleum ether (PE) was studied against field isolates of Ancylostoma duodenale collected and cultivated from hookworm infected human stool samples by egg hatch and larval motility assays. Major active compounds namely andrographolide (AP1), neoandrographolide (AP2) and andrograpanin (AP3) were estimated quantitatively in all the extracts by high-performance liquid chromatography (HPLC) and mass spectrometry (MS) analysis. Anthelmintic effects (ED50, LC50 ) and presence of the marker compounds in each extract was statistically analyzed by principal component analysis (PCA). Further, biological activities of pure compounds of AP1, AP2, AP3 were assessed to validate the results of the study. Results: Extracts in ethanol and methanol showed highest activity in inhibition of egg hatching with lowest ED50 values (0.017 and 0.02 mg/mL respectively) while ethyl acetate extract had the highest activity against larval motility (0.001 mg/mL) followed by ethanol (0.019 mg/mL). On HPLC analysis, andrographolide content (%), the major diterpene compound, in Met and Et was 0.85 and 1.43 respectively. On PCA, andrographolide component in the extracts was associated with significant inhibitory effects both on egg hatching and larval motility. Pure compound AP1 also showed significant ovicidal and larvicidal activities at concentrations 0.125 µg/mL and 0.019 mg/mL respectively. Conclusion: Andrographolide is one of the main phytochemical responsible for significant ovicidal and larvicidal activity against field isolates of A.duodenale from human infections and can be developed as a potential therapeutic choice. Graphical abstract: fx1